Towards an integrated sociotechnical framework for situation awarenss and decision-making for emergency care - Abd Hamid, Harris Shah; Waterson, Patrick (2010)
Emergency Care Practitioner (ECP) is a work role in the Ambulance Services in the UK that was introduced to provide an alternative emergency care within the community. In order to further understand the cognitive aspects of the work role, a study was carried out to identify factors influencing situation awareness and decision-making among ECPs in an Ambulance Service in England. Two ECPs participated in observations (40 hours of ride-outs) and semi-structured interviews. Analysis of the interview reveals factors that can be categorised into a number of systems-related levels of analysis (macro-micro). The outcomes from the study form the basis of an integrated sociotechnical system framework for emergency care with a focus on situation awareness and decision-making.